Combining aquatic physiotherapy with usual care physiotherapy for people with neurological conditions: A systematic review. (8th October 2019) - Moritz, Tamara A.; Snowdon, David A.; Peiris, Casey L.
Abstract: Objective: The objective of this review was to determine whether the combination of aquatic physiotherapy with usual care and results in greater improvements in activity limitations and neurological‐related impairments in individuals with neurological conditions than usual care physiotherapy alone. Methods: A systematic review of controlled trials was utilized to compare usual care physiotherapy with usual care physiotherapy combined with aquatic physiotherapy for adults with any neurological condition. Standardized mean differences and 95% confidence intervals were calculated from postintervention means and standard deviations. Results: Ten trials with a total of 490 participants met the inclusion criteria. Of the included trials, combined aquatic and usual care physiotherapy was evaluated in people with stroke in eight trials and in people with Parkinson's disease in two trials. Trial and outcome heterogeneity prevented the completion of meta‐analyses. Data from five trials ( n = 259) in people with stroke suggest that aquatic physiotherapy improves measures of balance, walking, mobility, and activities of daily living. No significant differences were detected in measures of activity limitation for people with Parkinson's disease nor measures of impairment for people with stroke or Parkinson's disease. Conclusion: This review provides preliminary evidence that the combination of aquatic physiotherapy with usual care physiotherapy may improve activity limitations in people with stroke. This review found no evidence to support the combination of aquatic physiotherapy with usual care physiotherapy to improve activity limitations in Parkinson's disease or other neurological populations. These results should be interpreted with caution due to the mixed quality of the included trials.